Controlling the Output Voltage of a Step Up-Down Five-Level Inverter - Leonardus Heru Pratomo; Slamet Riyadi; Agengkarunia Cahyadi Wibawa (Jurnal Teknik Elektro, 2023)
The increasing demand for electrical energy must be balanced with using renewable energy. However, the use of renewable energy requires a system to maximize the conversion of renewable energy into electrical energy. Various topologies have been studied to achieve maximum energy conversion. Two types of inverters, namely step up-down, have been widely used but have their respective limitations. Step-down inverters can only be used in lower output voltage than input voltage conditions with simple control, while step-up inverters can only operate in higher output voltage than input voltage conditions. This paper aims to combine these two converters to have both step-up-down voltage functions, with the goal of expanding the operating range and maintaining the advantages of each type. Thus, a topology called a step-up-down five-level inverter with a simple voltage-controlled capacitor balancing system is proposed in this paper. Finally, the simulation and laboratory tests were done. This inverter operates in step-up-down voltage, and the voltage in capacitors is always balanced to reach the desired level. The voltage control was done to get the constant voltage event the load was changed.